Cdk8 deletion in the ApcMin murine tumour model represses EZH2 activity and accelerates tumourigenesis. Issue 4 (24th September 2015) - McCleland, Mark L; Soukup, Tim M; Liu, Scot D; Esensten, Jonathan H; de Sousa e Melo, Felipe; Yaylaoglu, Murat; Warming, Soren; Roose‐Girma, Merone; Firestein, Ron
Abstract: CDK8 is a dissociable kinase module of the Mediator complex and has been shown to play an important role in transcriptional regulation in organisms as diverse as yeast and humans. Recent studies suggest that CDK8 functions as an oncoprotein in melanoma and colon cancer. Importantly, these studies were conducted using in vitro cell line models and the role of CDK8 in tumourigenesis in vivo has not been explored. We have generated a mouse with a Cdk 8 conditional knockout allele and examined the consequences of Cdk 8 loss on normal tissue homeostasis and tumour development in vivo . Cdk 8 deletion in the young adult mouse did not induce any gross or histopathological abnormalities, implying that Cdk 8 is largely dispensable for somatic cellular homeostasis. In contrast, Cdk 8 deletion in the Apc Min intestinal tumour model shortened the animals' survival and increased tumour burden. Although Cdk8 deletion did not affect tumour initiation, intestinal tumour size and growth rate were significantly increased in Cdk8 ‐null animals. Transcriptome analysis performed on Cdk8 ‐null intestinal cells revealed up‐regulation of genes that are governed by the Polycomb group (PcG) complex. In support of these findings, Cdk8 ‐null intestinal cells and tumours displayed a reduction in histone H3K27 trimethylation, both globally and at the promoters of a number of PcG‐regulated genes involved in oncogenic signalling. Together, our findings uncover a tumour suppressor function for CDK8 in vivo and suggest that the role of CDK8 activity in driving oncogenesis is context‐specific. Sequencing data were deposited at GEO (Accession No. GSE71385). Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.